A lightweight Color-changing melon ripeness detection algorithm based on model pruning and knowledge distillation: leveraging dilated residual and multi-screening path aggregation - Chen, Guojun; Hou, Yongjie; Chen, Haozhen; Cao, Lei; Yuan, Jianqiang (Frontiers in Plant Science, 2024)
Color-changing melons are a kind of cucurbit plant that combines ornamental and food. With the aim of increasing the efficiency of harvesting Color-changing melon fruits while reducing the deployment cost of detection models on agricultural equipment, this study presents an improved YOLOv8s network approach that uses model pruning and knowledge distillation techniques. The method first merges Dilated Wise Residual (DWR) and Dilated Reparam Block (DRB) to reconstruct the C2f module in the Backbone for better feature fusion. Next, we designed a multilevel scale fusion feature pyramid network (HS-PAN) to enrich semantic information and strengthen localization information to enhance the detection of Color-changing melon fruits with different maturity levels. Finally, we used Layer-Adaptive Sparsity Pruning and Block-Correlation Knowledge Distillation to simplify the model and recover its accuracy. In the Color-changing melon images dataset, the mAP@0.5 of the improved model reaches 96.1%, the detection speed is 9.1% faster than YOLOv8s, the number of Params is reduced from 6.47M to 1.14M, the number of computed FLOPs is reduced from 22.8GFLOPs to 7.5GFLOPs. The model's size has also decreased from 12.64MB to 2.47MB, and the performance of the improved YOLOv8 is significantly more outstanding than other lightweight networks. The experimental results verify the effectiveness of the proposed method in complex scenarios, which provides a reference basis and technical support for the subsequent automatic picking of Color-changing melons.